Clinical and Angiographic Results of Intra-Aneurysmal Embolization for Cerebral Aneurysms and Histopathological Findings in an Aneurysm Treated with GDC - Kaku, Y. (Centauro S.r.l., 2003)
We describe follow-up clinical and angiographic results in patients with cerebral aneurysms treated with IDC or GDC. In 175 patients, 116 patients with ruptured aneurysm and 59 patients with non-ruptured aneurysm who underwent endovascular occlusion of aneurysms, there was no mortality and nine cases (4.7%) with morbidity in the periprocedural period. During follow up period, four cases (2.3%) experienced bleeding, and three cases (1.7%) experienced thrombo-embolic events. On the follow-up angiograms (median angiographic follow-up period 24.8 months), 12.5% of incompletely obliterated aneurysms exhibited progressive thrombosis, 20% remained unchanged and 67.5% showed aneurysmal recanalization or regrowth. Histological examination of a small ruptured A-com aneurysm treated seven months before harvesting, demonstrated that formation of an incomplete endothelium-lined layer of connective tissue at the orifice, and no complete fibrous obliteration of the aneurysm lumen could be detected, various amounts of unorganized clot were still present in the center of the aneurysm. Coil embolization is a safe treatment for cerebral aneurysms with a lower incidence of periprocedural morbidity, wheareas follow-up results are less satisfactory in cases involving incompletely obliterated lesions.